PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN SEKOLAH DENGAN RAPID APPLICATION DEVELOPMENT - Ariyati, Indah (LPPM Universitas Nusa Mandiri, 2018)
The school library becomes a benchmark of the students' progress. Management and service in the library should always be controlled, for example when adding books, adding members, borrowing transactions and return transactions up to the report. Data members and data books that have not been stored properly, the transactions of borrowing and returns are still manual so that no detection of fine either penalty delay, damaged and even lost. Therefore, the authors build school library information system using Microsoft Visual Basic 6.0 programming language. The author builds a computerized system in order to know the suitability between the borrowing time and the payback time as well as the amount of the fine imposed upon the return of the book. Development of a computerized system using Unified Modeling Language (UML). By building a computerized system it can process and store data well so that it provides complete, accurate and timely information.